Molecular Genotyping of Microbes by Multilocus PCR and Mass Spectrometry: A New Tool for Hospital Infection Control and Public Health Surveillance - Ecker, David J. (Molecular Epidemiology of Microorganisms, 2009)
We describe a new technology for the molecular genotyping of microbes using a platform known commercially as the Ibis T5000. The technology couples multilocus polymerase chain reaction (PCR) to electrospray ionization/mass spectrometry (PCR/ESI-MS) and was developed to provide rapid, high-throughput, and precise digital analysis of either isolated colonies or original patient specimens on a platform suitable for use in hospital or reference diagnostic laboratories or public health settings. The PCR/ESI-MS method measures digital molecular signatures from microbes, enabling real-time epidemiological surveillance and outbreak investigation. This technology will facilitate understanding of the pathways by which infectious organisms spread and will enable appropriate interventions on a time frame not previously achievable.